Overexpression of microRNA-21 decreased the sensitivity of advanced cervical cancer to chemoradiotherapy through SMAD7. Issue 3 (March 2020) - Liu, Qifang; Liu, Shuang; Wang, Danbo
Abstract : Drug resistance is a major problem in the treatment of advanced cervical cancer. The oncogenic microRNA-21 (miR-21) is involved in drug resistance in various cancers. However, the regulatory role of miR-21 and its target, Smad7 in drug resistance of cervical cancer remains to be elucidated. We compared miR-21 and Smad7 levels in human samples from chemoradiotherapy-resistance cervical cancer (resistant group) and chemoradiotherapy-sensitive cervical cancer (sensitive group) patients. Then, the miR-21 level was manipulated in HeLa and SiHa cervical cancer cells and the Smad7 level was determined by PCR and western blot. We also manipulated miR-21, Smad7 or both in cells, and measured cell viability using cell counting kit-8 method and epithelial–mesenchymal transition (EMT) biomarkers using Western blot. In human samples, resistant group has significantly higher miR-21 and lower Smad7 levels than sensitive group. In-vitro analysis demonstrated downregulated Smad7 after transfection with miR-21 mimics. When cells were transfected with Smad7 inhibitor, we observed increased drug resistance and changed levels of EMT-biomarkers after chemoradiotherapy, suggesting that downregulation of Smad7 decreased the sensitivity through EMT. When the cells were transfected with miR-21 inhibitor alone, we found increased sensitivity to chemoradiotherapy through EMT. However, such effects were attenuated when Smad7 was also downregulated after cotransfection. In summary, we provided clinical and experimental evidence that decreased miR-21 may improve drug resistance through EMT by direct targeting Smad7 in cervical cancer. Our data suggest that miR-21/Smad7 pathway may be an effective target for drug resistance in cervical cancer treatment.